What drives long-term trends in newly retired women's and men's economic independence? An analysis of contemporary and historical determinants - Laure Doctrinal (Luxembourg Income Study (LIS), 2023)
Concerns about the social sustainability of pension systems are growing. The increasing privatization of pension provision in many OECD countries is expected to have harmful consequences for workers with non-standard working careers, among whom women are overrepresented. Despite much new research, little is known about changes in the incomes of newly retired persons. Using microdata from the Luxembourg Income Study, this study analyzes how the economic independence of newly retired women and men has changed over the years 1986-2018 in fifteen OECD countries and assesses some of its determinants. The results show that economic independence among newly retired women has increased since the 1980s in almost all countries, but decreased among men in half of the countries considered here. Regression analyses show that pension privatization is not associated with worsened economic independence among newly retired women, nor among newly retired men. Minimum public pensions tend to increase the economic independence of both newly retired women and men. Economic independence is also more common among newly retired cohorts of women with gainful work histories and parental leave duration in their prime working years.
Keywords: 330